Materiais convencionais utilizados na construção civil e emissão de CO2 : estudo de caso de um edifício educacional da UTFPR - Deeke, Vania (2009)
In face of natural disasters caused by global warming and several environmental problems, immediate actions are necessary. The building and construction industry causes heavy environmental impact, particular the GHG- Greenhouse Gases, more specific the CO2.This research, primarily quantifies the CO2 emissions from the envelope of a Educational Building, located at Ecoville Campus, at UTFPR University, in Curitiba, Paraná. After that, propose “alternative materials” instead the “conventional materials”. The research is delimited into the emissions of the preoperate phase and exalts the important role of the specification from the building materials to the reduction CO2 emissions goal. The results are discussed trough a systemic approach inherent to the sustainability. The Scene 01- formed by the “conventional materials”- produce 236 586kg CO2 and the Scene 02 – formed by “alternative materials” totalized 84 823kg CO2, obtaining a reduction from 151 763 kgCO2. The brick of soil cement and the wood have a significant role on this result, the first one because does not needs burning and the wood because captures CO2. At the same time that intends to collaborate with the development of process to reduce the CO2 emissions, this research also intends to contribute to the creation of a “sustainability culture. A building can be a sustainability icon through its semiotic language, the spreading of new technologies, concepts and practices that, associated to the responsibility of a Technological University, can stimulate sustainable construction. In addition to its explicit curriculum, every higher education institution has an implicit curriculum consisting of its grounds, buildings and operations – based on analyses that show the urgency of assimilating sustainable practices through the buildings and operations at the campus, using their design and operational routine as an educational tool.